Qohelet. Analisi sintattica, traduzione, composizione - Niccacci, A. (Liber Annuus, 2004)
Abstract Following his article in LA 52 (2002) 29-102, the author analyzes the Book of Qohelet from the point of view of syntax, translation, and literary composition. A main result of his analysis is that the verb system of classical Hebrew is kept throughout the book and there is no evidence of a late date from this point of view. Further, the analysis of the verb syntax provides an essential key to the literary structure and the interpretation of the book. The complete Hebrew text with accompanying Italian translation is given in parallel columns according to the following literary composition: a frame, 1:1-11 // 12:8-14; the body with two main parts, each comprising five subsections: (I/1) 1:12–2:26 // (II/1) 7:15-29; (I/2) 3:1-22 // (II/2) 8:1-15; (I/3) 4:1-16 // (II/3) 8:16–9:10; (I/4) 4:17–5:19 // (II/4) 9:11–10:4; (I/5) 6:1-9 // (II/5) 10:5-19; and a central subsection, 11:7–12:7.